2020
DOI: 10.1186/s12909-020-02101-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of faculty on mentorship: an exploratory interpretivist study at a sub-Saharan African medical school

Abstract: Background: Mentorship has become a routine part of undergraduate training in health professions education. Although many health professions training institutions have successfully incorporated faculty-student mentorship in their formal training, many others especially in Sub-Saharan Africa have not fully embraced this. Institutionalized mentorship programmes are effective methods of enhancing student learning experiences. Faculty, who are the mentors have an active role to play in driving the mentorship agend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Besides, the study also revealed that more than half of the nurses have a good opinion of mentoring, are ready for training, and are willing to practice mentee-mentor relationships. Some study findings back up the aforementioned report, where the majority of the respondents showed readiness to practice clinical mentorship if instituted (Mariani 2012;Mubuuke et al, 2020;Rohatinsky et al 2013).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Besides, the study also revealed that more than half of the nurses have a good opinion of mentoring, are ready for training, and are willing to practice mentee-mentor relationships. Some study findings back up the aforementioned report, where the majority of the respondents showed readiness to practice clinical mentorship if instituted (Mariani 2012;Mubuuke et al, 2020;Rohatinsky et al 2013).…”
Section: Discussionmentioning
confidence: 62%
“…However, a survey carried out in the 3 Article DOI: 10.52589/AJHNM_Q050T41M DOI URL: https://doi.org/10.52589/AJHNM_Q050T41M www.abjournals.org Northern part of Nigeria to evaluate the knowledge of health workers on clinical mentoring, revealed inadequate knowledge during pre-evaluation, with a significant increase in the score of post-exposure to clinical mentoring training (Okereke et al, 2015). A related study in Sub-Saharan African medical school reports that majority of the faculty members are less knowledgeable on mentorship regardless of seniority (Mubuuke et al, 2020). In contrast to the above, a study done in Rwanda among the registered nurses shows adequate knowledge of clinical mentorship, and 90% claimed to be familiar with clinical mentorship (Kagabo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most medical schools in developing countries like in sub-Saharan Africa lack or poorly implement these mentorship programs and most of students and staffs in those institutions are neither aware nor practicing mentorship programs 7 , 8 . There is a need for revival and reformation towards mentorship programs in such institutions.…”
Section: Mentorship Programs and Medical Schoolsmentioning
confidence: 99%
“…Mentoring and leadership training are often not part of the undergraduate and postgraduate medical training curriculum in many sub-Saharan African countries [35,36]. This puts further strain in the leadership pool available for healthcare delivery in the subcontinent.…”
Section: Leadership Challenges In Health Institutions Across Sub-saha...mentioning
confidence: 99%